(3JgPjH eSJeQ GdChgGe Ydi Phi GdeYQaI hChdi GdCagGes - (3Ydj Hf gHI Gddg Hf Ydj Hf LYaQ, CHh fUQ, SYO Gdedc, GHf eGchdG,J (B475 (3g` s; (3HOQ Hf ESeGYjd GdJHQjRj, HOQ GdOjfs
(3ChdgG (B:s
(3GdMeO ddg GdPi JaQO HGdceGd adG fbU ai JeGeg EdN s
(3hgh ZjQ cJGH GdGceGd GdcHjQ dgddeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B40s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B45 s
(3eUOQ GbJfGA GdCUd (B:s
(3ajV Gddg (B(1584) s
Keywords: (3GdJGQjNs